The Influence of Product Quality and Brand Image on The Purchasing Decision of The Santri Brand Bottled Drinking Water in Sidoarjo Regency, East Java Province - Nirmala, Syifa Faizah; Suranto, S (Universitas Muhammadiyah Surakarta, 2022)
This research aims to determine the influence of product quality and brand image on purchasing decisions of Santri brand bottled drinking water in Sidoarjo Regency. This is survey research using a quantitative approach. The sample of this research consisted of 100 consumers of Santri bottled drinking water selected through the purposive sampling method. The inclusion criteria were the consumers who regularly purchased this brand product. Data were collected through a questionnaire. To analyze the data, multiple regression analysis, t-test, F-test, coefficient of determination (R2), effective contribution, and relative contribution were used. The results showed that there was a partial and simultaneous relationship between product quality and brand image variables on purchasing decisions. These two variables contributed 56.8% to purchasing decisions.